Knowledge, Attitudes, and Practices of NICU Doctors and Nurses Toward Prevention and Control of Nosocomial Infection With Multidrug Resistant Organism - Zhou, Jinyan; Chen, Shuohui (Frontiers in Pediatrics, 2022)
Background: Nosocomial infection with multi-drug resistant organisms (MDRO) can directly influence the curative effect and prognosis of neonates, bringing great difficulties to clinical treatment. As direct contacts of neonates, the knowledge, attitudes and practices (KAP) of doctors and nurses are critical for prevention and control of MDRO infection in neonatal intensive care units (NICUs). Purpose: To describe the KAP of doctors and nurses in NICUs towards prevention and control of nosocomial infection with MDRO and to analyse its influencing factors. Methods: This cross-sectional study used convenience sampling to survey 397 doctors and nurses from the NICU of 28 hospitals in 11 cities in Zhejiang Province, China. Univariate analysis and multiple linear regression were used to analyse the data. Results: The median scoring rate (interquartile range) of knowledge, attitude and practice questionnaire was 0.86 (0.82-0.91), 0.98 (0.91-1.00) and 1.00 (0.97-1.00), respectively. However, the median scoring rate regarding “basic knowledge of MDRO” and “special prevention and control measures” was 0.50 in knowledge. Multiple linear regression showed that the influencing factors of KAP were hospital grade, professional title, gender, regular supervision and training. Conclusions: There was still room for improvement in the KAP of NICU doctors and nurses, especially regarding the knowledge. Male gender, doctors and nurses in lower-grade hospitals and with low professional titles had worse KAP. Training and supervision helped improve the KAP. Relevance to Clinical Practice: In order to improve the KAP of doctors and nurses to enhance the prevention and control effect for MDRO in NICU’s, hospitals and departments should carry out targeted training and strengthen supervision, while lower-grade hospitals, male and doctors and nurses with low professional titles need more attention.